2014
DOI: 10.1093/mnrasl/slu184
|View full text |Cite
|
Sign up to set email alerts
|

Binary black hole accretion during inspiral and merger

Abstract: We present the results of 2D, moving mesh, viscous hydrodynamical simulations of accretion onto merging supermassive black hole (SMBH) binaries. We include viscous heating, shock heating, and radiative cooling, and simulate the transition from the "pre-decoupling" epoch, where the inspiral timescale is longer than the viscous timescale, to the "post-decoupling" epoch, where the inspiral timescale is shorter than the viscous timescale. We find that there is no abrupt halt to the accretion at decoupling, but rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
175
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(183 citation statements)
references
References 38 publications
8
175
0
Order By: Relevance
“…D 'Orazio et al (2015) showed that, under the assumption that the optical period corresponds to the longer period of the hotspot in the accretion disk, PG1302 would be in the gravitational inspiral regime. This would confirm that SMBHBs can produce bright electromagnetic emission even at these late stages of the merger (Noble et al 2012;Farris et al 2015).…”
Section: Introductionmentioning
confidence: 59%
“…D 'Orazio et al (2015) showed that, under the assumption that the optical period corresponds to the longer period of the hotspot in the accretion disk, PG1302 would be in the gravitational inspiral regime. This would confirm that SMBHBs can produce bright electromagnetic emission even at these late stages of the merger (Noble et al 2012;Farris et al 2015).…”
Section: Introductionmentioning
confidence: 59%
“…In contrast, recent Newtonian simulations (see, e.g. (Farris et al 2014;Muñoz & Lai 2016)) have clearly demonstrated that individual "mini-disks" form around each BH over many binary orbital periods.…”
Section: Introductionmentioning
confidence: 86%
“…However, a few years ago multi-dimensional numerical simulations of circumbinary disks with internal stresses showed that streams of gas are, in fact, readily peeled off the inner edges of such disks (MacFadyen & Milosavljević 2008;Shi et al 2012;Noble et al 2012;D'Orazio et al 2013). More recently, simulations with carefully defined external accretion rates have shown that essentially all the mass passing through the circumbinary disk is conveyed to the binary (Farris et al 2014;Shi & Krolik 2015). Shi & Krolik (2015) showed in detail how binary torques acting on streams in the gap can drive gas back out to the circumbinary disk, where a portion of the streams' mass loses enough of its angular momentum by shock deflection that it then falls directly to the binary.…”
Section: Introductionmentioning
confidence: 99%
“…Recent simulations (Noble et al 2012;Farris et al 2015a) show that high levels of accretion can persist well past the decoupling phase, delivering gas to the binary efficiently until much closer to coalescence. These simulations also exhibit the lopsided cavity which generates the χt bin variability considered here.…”
Section: Binary-disc Decouplingmentioning
confidence: 99%